A single‐centre, open‐label, prospective study of an initially short‐term intensified dosing regimen of enteric‐coated mycophenolate sodium with reduced cyclosporine A exposure in Chinese live‐donor kidney transplant recipients. (April 2014) - Cai, L.; Zeng, F.; Liu, B.; Wei, L.; Chen, Z.; Jiang, J.
Summary: Aims: The nephrotoxicity of cyclosporine A (CsA) accounts for dysfunction of kidney allografts in the clinic. Short‐term intensified dosing using enteric‐coated mycophenolate sodium (EC‐MPS) may facilitate CsA sparing after kidney transplantation without compromising safety. Methods: In a 12‐month, single‐centre open‐label prospective trial, 180 de novo live‐donor kidney transplant recipients at low‐immunological risk were randomised to a low‐dose cyclosporine group which received a low dose of cyclosporine, short‐term intensified EC‐MPS dosing (2160 mg/day to week 6, 1440 mg/day thereafter) and corticosteroids or a standard‐dose cyclosporine group which received a standard dose of cyclosporine, standard EC‐MPS dosing (1440 mg/day) and corticosteroids. The primary end‐point [treatment failure including biopsy‐proven acute rejection (BPAR), graft loss, death], secondary end‐point and adverse events were monitored. Results: The primary end‐point (treatment failure) occurred in 13.3% (12/90) of the low‐dose cyclosporine group and 16.7% (15/90) of the standard‐dose cyclosporine group (p = 0.53) (difference −3.4%, 95% confidence interval −11.7% to 7.5%, based on a noninferiority margin of 20%). BPAR occurred in 11.1% and 13.3% of patients in the low‐dose cyclosporine group and standard‐dose cyclosporine group, respectively (p = 0.65). The estimated glomerular filtration rate, as calculated by the Cockcroft–Gault formula, was similar at 12 months after transplantation (low‐dose cyclosporine group 63 ± 19 ml/min/1.73 m 2 and standard‐dose cyclosporine group 59 ± 15 ml/min/1.73 m 2 ; p = 0.43). The levels of serum creatinine and occurrence of adverse events between the two groups were not statistically different. Conclusions: A regimen of early intensified EC‐MPS dosing permits low‐dose cyclosporine in live‐donor kidney transplant patients at low‐immunological risk without compromising efficacy at 12 months' follow‐up.